The Effect of Compensation and Emotional Intelligence on Employee Performance with Job Satisfaction as an Intervening Variable - Rizqiyyah; Andreas Wahyu Gunawan P (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of Compensation and Emotional Intelligence on Employee Performance with Job Satisfaction as an intervening varible for employees of the Tangerang Manufacturing Industry.The Research methodology is through a questionnaire survey to collect data to test the research hypothesis. The type of research used is quantitative with Structural Equation Modeling (SEM) approach using Analysis of Structural Moments (AMOS). The sample used in this study was 150 employees of a Manufacturing Industry Company in Tangerang. The results of the study have five hypotheses and all of them are supported, which states that there is an effect of Job Satisfaction as an intervening variable between Compensation and Emotional Intelligence on Employee Performance. Managerial implications in this study, it is hoped that related companies can pay more attention to the long term impact regarding emotional intelligence this is done so that there is no miss communication between employees so that employees can provide good employee performance. manufacturing industry companies need to reevaluate the suitability between compensation and the workload given, especially on overtime wages in order to have a positive impact in increasing employee performance. manufacturing industry companies need to pay more attention to employee job satisfaction that increase worker productivity, can be done by providing work motivation to employees for example providing rewards so that employees feel appreciated, this can affect employee performance.